Beyond the Pathogen Cultural Influences on the Impact of Epidemics Viewed from History - Newson, Linda A. (Philippine Studies: Historical and Ethnographic Viewpoints, 2020)
The paper reflects on the historical experience of epidemics in Latin America and the Philippines. It shows how cultural factors can affect the ability of societies to develop immunity and recover. It also shows how leadership can influence the way in which an epidemic and the health crisis is managed. As such, it argues that the impact of a single epidemic is unlikely to be the same throughout the world or even within one country